Mechanisms of left ventricular systolic dysfunction in light chain amyloidosis: a multiparametric cardiac MRI study - Katznelson, Ethan; Jerosch-Herold, Michael; Cuddy, Sarah A. M.; Clerc, Olivier F.; Benz, Dominik C.; Taylor, Alexandra; Rao, Shivani; Kijewski, Marie Foley; Liao, Ronglih; Landau, Heather; Yee, Andrew J.; Ruberg, Frederick L.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Cardiac systolic dysfunction is a poor prognostic marker in light chain (AL) cardiomyopathy, a primary interstitial disorder; but its pathogenesis is poorly understood. Purpose: To analyze the effects of extracellular volume (ECV) expansion, a surrogate marker of amyloid burden on myocardial blood flow (MBF), myocardial work efficiency (MWE), and left ventricular (LV) systolic dysfunction in AL amyloidosis. Methods: Subjects with biopsy-proven AL amyloidosis were prospectively enrolled (April 2016 to June 2021; Clinicaltrials.gov ID NCT02641145) and underwent cardiac magnetic resonance imaging (MRI) to quantify rest MBF by perfusion imaging, LV ejection fraction (LVEF) by cine MRI, and ECV by pre- and post-contrast T1 mapping; MWE was estimated as external cardiac work from stroke volume and mean arterial pressure, normalized to LV myocardial mass. Results: Rest MBF in 92 subjects (62±8 years, 52 men) with AL amyloidosis averaged 0.87±0.21 ml/min/g and correlated with MWE (r=0.42; p<0.001). Rest MBF was similarly low in subjects with sustained hematologic remission after successful AL amyloidosis therapy (n=21), as in those with recently diagnosed AL amyloidosis. Both MBF and MWE decreased by ECV tertile (p<0.01 for linear trends). The association of ECV with MWE comprised a direct effect (84% of total effect; p<0.001) on MWE from adverse interstitial remodelling assessed by ECV, and an indirect effect (16% of total effect; p<0.001) mediated by MBF. There was a significant base-to-apex gradient of rest MBF in subjects with higher amyloid burden. Conclusions: In AL amyloidosis, myocardial blood flow and myocardial work efficiency are reduced with increasing cardiac amyloid burden and ECV expansion. Both structural and vascular changes from extracellular volume expansion and myocardial amyloid burden appear to contribute to lower MWE.